Serum Calcium Levels and Parkinson’s Disease: A Mendelian Randomization Study - Wang, Yanchao; Gao, Luyan; Lang, Wenjing; Li, He; Cui, Pan; Zhang, Nan; Jiang, Wei (Frontiers in Genetics, 2020)
Background: Previous epidemiological studies evaluated the relationship between serum calcium content and Parkinson’s disease (PD), while the results demonstrated by these studies were often inconsistent. At present, whether there is a causal relationship between serum calcium content and PD is still not clear. Objective and Methods: Therefore, the objective of this study was to explore the relationship between increased serum calcium content and PD risk. In this present study, a Mendelian randomization trial was carried out by using a large-scale serum calcium genome-wide association study (GWAS) dataset (N=61,079, Europeans) and a large-scale PD GWAS dataset (N=8,477, Europeans including 4238 PD patients and 4239 controls). Here, a total of four Mendelian randomization methods including weighted median, inverse-variance weighted meta-analysis (IVW), MR-Egger, and MR-PRESSO were used. Results: Our data together indicated that increased serum calcium content could be not significantly related to PD. Conclusions: In conclusion, we provided genetic evidence that there was not direct causal relationship between serum calcium levels and PD. Hence, calcium supplementation might not contribute to reduce PD risk.